Seasonal variation changes in biosynthesis of Nanoparticles by mangroves (Funded Work) - ASMATHUNISHA.N,; KATHIRESAN.K, (International Journal of Pharma and Bio Sciences, 2018)
The mangroves are growing in a dynamic coastal environment with ever changing conditions of temperature, tidal water, salinity and others. In order to adapt to the varying conditions, mangroves produce a variety of chemicals. The chemicals are of different biological activities including nanoparticle synthesis. The nanoparticle synthesis depends on the concentration of chemicals that are responsible for biosynthesis and hence the biosynthesis of nanoparticles may have seasonal variation with the plants sample used. Several chemical factors such as pigments, alkaloids, polyphenols and proteins do determine the synthesis of nanoparticles. In order to test this hypothesis the present work was undertaken to study the seasonal variations of mangroves on synthesis of nanoparticles. The present study proved that phenols present in the mangrove plant sample were found mostly responsible for the nanoparticle synthesis. The synthesis of nanoparticles was higher in X. mekongensis followed by R. annamalayana. The nanoparticles synthesis was high in monsoon but low in summer. The colour formation was very quick in monsoon but very slow in summer. Similarly, the colour formation was very high in silver followed by gold.